2011
DOI: 10.1002/er.1880
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced hydrogen on iron hexagonal mesoporous silica (Fe-HMS) photo-catalyst

Abstract: SUMMARY The iron hexagonal mesoporous silica (Fe‐HMS)‐n photocatalyst, where n is the molar ratio Si/Fe in the precursor gel (=50), has been successfully synthesized at an ambient temperature using hexadecylamine as template agent. The material was characterized by X‐ray diffraction, N2 adsorption measurement Brunauer, Emmet, Taller (BET) and Barrett–Joyner–Halenda theory, UV–Vis spectroscopy, high‐resolution transmission electron microscopy and electron spin resonance. The electrical conductivity follows an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Zn-doped SBA-15 mesoporous silica was found also to be a good support for CdS photocatalysts because of its particle sieving ability to immobilize the sizequantized CdS nanoparticles selectively and to archive a well-defined nanostructure [25]. Photocatalytic generation of hydrogen on Zr-MCM-41 [26], CdS/Al-HMS [27] and Fe-HMS [28] was also reported.…”
Section: Introductionmentioning
confidence: 91%
“…Zn-doped SBA-15 mesoporous silica was found also to be a good support for CdS photocatalysts because of its particle sieving ability to immobilize the sizequantized CdS nanoparticles selectively and to archive a well-defined nanostructure [25]. Photocatalytic generation of hydrogen on Zr-MCM-41 [26], CdS/Al-HMS [27] and Fe-HMS [28] was also reported.…”
Section: Introductionmentioning
confidence: 91%
“…Conversely, among the AOPs is a photo‐catalysis process, heterogeneous and homogeneous photo‐catalysis which is based on the irradiation and on the catalyst with a semi‐conductor property . An efficiency and successful application of photo‐catalysis depend on the interaction between pollutant and catalyst at the interface semiconductor/electrolyte and also on the irradiation source.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper, we reported a study of iron particles prepared by a microwave–hydrothermal method. The results revealed that the presence of iron nanoparticles enhanced visible light irradiation properties via water reduction []. However, nanoparticles and bulk sample comparison showed a large amount of H 2 using a water splitting process .…”
Section: Introductionmentioning
confidence: 99%